Sanitary Design and Construction of Food Equipment - Ronald H. Schmidt; Daniel J. Erickson (EDIS)
To ensure safe food and adequate sanitation programs, the equipment used for processing and handling food products must be designed, fabricated, constructed, and installed according to sound sanitary design principles. This ensures the equipment can be adequately cleaned and sanitized, and that surfaces are resistant to daily exposure to corrosive food products and cleaning/sanitizing chemicals. Equipment that does not meet basic sanitary design principles, or is installed or used improperly cannot be adequately cleaned and sanitized. This document is FSHN04-09, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 2005.